Harder, better, faster, stronger? Retrospective chart review of adverse events of interactions between adaptogens and antidepressant drugs - Siwek, Marcin; Woroń, Jarosław; Wrzosek, Anna; Gupało, Jarosław; Chrobak, Adrian Andrzej (Frontiers in Pharmacology, 2023)
Aim: We aimed to systematically evaluate the prevalence and clinical characteristics of adverse events associated with the adaptogens and antidepressant drug interactions in a retrospective chart review. Methodology: A total of 1,816 reports of adverse events were evaluated. Cases were included in the analysis if the pharmacoepidemiological analysis showed the presence of a high probability of a causal relationship between an adaptogen and antidepressant interaction and the occurrence of adverse events. The following data were extracted from the reports: age, sex, antidepressant, plant products containing adaptogens, other concomitant medications, and clinical consequences of the interactions and their possible mechanisms. Results: Adaptogens were involved in 9% of adverse events associated with the concomitant use of antidepressants and other preparations. We identified 30 reports in which side effects presented a causal relationship with the use of antidepressants and adaptogens. Here, we present the list of adaptogens with the corresponding antidepressants and the side effects caused by their interactions: Withania somnifera: reboxetine (testicle pain and ejaculatory dysfunctions), sertraline (severe diarrhea), escitalopram (myalgia, epigastric pain, nausea, vomiting, restless legs syndrome, and severe cough), and paroxetine (generalized myalgia, ophthalmalgia, and ocular hypertension); Eleutherococcus senticosus: duloxetine (upper gastrointestinal bleeding), paroxetine (epistaxis), sertraline (vaginal hemorrhage), and agomelatine (irritability, agitation, headache, and dizziness); Schisandra chinensis: bupropion (arthralgia and thrombocytopenia), amitriptyline (delirium), and fluoxetine (dysuria); Tribulus terrestris: citalopram (generalized pruritus), escitalopram (galactorrhea), and trazodone (psoriasis relapse); Coptis chinensis: mianserin (arrhythmias), mirtazapine (edema of lower limbs and myalgia), and fluoxetine (gynecomastia); Cimicifuga racemosa: mianserin (restless legs syndrome), paroxetine (gynecomastia and mastalgia), and venlafaxine (hyponatremia); Bacopa monnieri: agomelatine (back pain and hyperhidrosis) and moclobemide (myocardial infarction); Gynostemma pentaphyllum: duloxetine (back pain); Cordyceps sinensis: sertraline (upper gastrointestinal bleeding); Lepidium meyenii: mianserin (restless legs syndrome); and Scutellaria baicalensis: bupropion (seizures). Conclusion: Clinicians should monitor the adverse events associated with the concomitant use of adaptogens and antidepressant drugs in patients with mental disorders. Aggregation of side effects and pharmacokinetic interactions (inhibition of CYP and p-glycoprotein) between those medicines may result in clinically significant adverse events.